The medial sural artery perforator (MSAP) flap: A versatile flap for lower extremity reconstruction. Issue 4 (April 2020) - Al-Himdani, Sarah; Din, Asmat; Wright, Thomas C.; Wheble, George; Chapman, Thomas W.L.; Khan, Umraz
Abstract: Background: The medial sural artery perforator (MSAP) flap provides a thin, pliable and durable soft tissue reconstruction with adequate pedicle length and low donor morbidity. It is an ideal choice for small-to-moderate defects of the lower extremity, although it does have limitations. We report our experience of the flap in a three-pronged anatomical, clinical and patient reported outcome-based study. Methods: Cadaveric fresh frozen lower limbs ( n  = 10) were used for anatomical dissections to assess pertinent and clinically relevant findings. Data relating to MSAP flaps was collected from a prospectively maintained database over a 2-year period. Both clinical data and modified Enneking scores were analysed. Results: Anatomical study: A mean of 2.1 ± 0.99 perforators arose from the medial sural artery, located 11.9 cm ± 2.07 along the line between the popliteal fossa and medial malleolus. The largest perforator was located 13.58 cm ± 2.01 from the popliteal artery. The distance from the dominant perforator to the first branching point within the gastrocnemius was 7.39 ± 1.50 (range 5–9.2 cm). The short saphenous vein was located on average 3.08 cm ± 0.77 from the dominant perforator. Clinical study: Twenty free and nine pedicled MSAPs were included ( n  = 29). Open lower limb fractures ( n  = 18, 62%) and infection ( n  = 10, 35%) were the most common aetiologies. Defects sites included: foot-and-ankle ( n  = 12, 55%), knee ( n  = 9, 31%) and anterior leg ( n  = 4, 14%). Four patients (14%) required SSG to for donor site coverage. Venous congestion was responsible for partial flap necrosis in 6.9%( n  = 2) of patients. All wounds were healed at discharge. At 14 months, the mean Enneking score was 72.5%. All patients were ambulant, 96% returned to work and 87% were using pre-operative footwear. Conclusions: The MSAP provides robust foot-and-ankle reconstruction, whilst permitting glide when over the knee. Patient satisfaction and functional outcomes are excellent with careful patient selection. Care should be taken to avoid compression or kinking of the large, thin walled veins as the most commonly observed complication was venous congestion. We advocate MSAP as a first choice flap for small-to-moderate foot, ankle or knee defects.